Decision Support System for Determining Achievement Teachers Using Fuzzy-Analytical Hierarchy Process (F-AHP) (Case Study: SMP IT Khairunnas Bengkulu) - Migi Migi; Siswanto Siswanto; Jhoanne Fredricka (Penerbit Jurnal Indonesia, 2021)
Assessment of outstanding teachers aims to increase teacher productivity in the teaching and learning process. There are 4 criteria that are assessed, namely understanding of students, designing lesson plans, evaluating learning outcomes, and developing students. However, all of the outstanding teacher assessment processes still use Office Word and Excel applications, so it takes a long time because there is no structured database that can help store data so as to simplify the data processing process. This application is made using Visual Basic .Net programming language and SQL Server 2008r2 database, where the application has implemented one of the Decision Support System Methods, namely Fuzzy-Analytical Hierarchy Process (F-AHP). The data of outstanding teachers who were assessed were 10 people, processed into the Fuzzy-Analytical Hierarchy Process (F-AHP) method with the stages of determining the type of criteria, making alternative criteria, determining the pairwise comparison matrix, determining the comparison matrix of F-AHP criteria, determining the value of the synthesis, determine the value of vector (V) and fuzzy ordinate value (d'), calculation of weights and normalization of weight vectors, normalization results, as well as ranking and decision results. So as to produce the final score of the teacher's assessment with the highest score of 91.66. Based on calculations from assessment data that has been tested the Fuzzy-Analytical Hierarchy Process (F-AHP) method is able to provide appropriate and appropriate recommendations and can assist in the assessment of outstanding teachers at SMP IT Khairunnas Bengkulu.